Antibacterial Potential of Single Black Garlic Extract Organosulfur Compounds on Staphylococcus aureus Bacteria - Destiana, Rindy Tya; Herdyastuti, Nuniek; Setyarini, Wahyu; Arizandy, Radita Yuniar (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Single black garlic (SBG) is a product of processing garlic (Allium sativum L.) by heating it for several days. SBG has antibacterial activity due to the presence of organosulfur, phenolic and flavonoid compounds. This research aims to determine the antibacterial potential of SBG extract on Staphylococcus aureus and determine its chemical compound content based on Liquid Chromatography-Mass Spectrometer (LC-MS) analysis. The extract was obtained from the maceration method combined with a magnetic stirrer using 0, 30, 60 and 90% ethanol solvent. The antibacterial test used the disc diffusion method with a positive control of ciprofloxacin and a negative control of distilled water. LC-MS analysis of SBG extract with the best antibacterial activity. The results of the antibacterial activity test showed that the SBG extract had antibacterial activity based on the presence of an inhibition zone. The largest zone of inhibition in the 90% ethanol solvent SBG extract was 27.71 mm, and the positive control was 22.58 mm. The SBG extract with the most optimal antibacterial activity was analyzed using LC-MS to produce 109 compounds which were divided into 15 different compound groups, some of which were allicin (5.900%) which was the compound with the most composition and innulotetraose (0.065%) which was the compound with the smallest composition in the SBG extract. Data from the antibacterial test results were processed using the IBM statistical program SPSS 25, a One-way ANOVA test, which aims to determine the effect of antibacterial activity on Staphylococcus aureus bacteria, and data on the chemical compound content of the SBG extract were analyzed descriptively. SBG extract has the potential as an antibacterial which is classified as very strong in-vitro, so further in-vivo research is needed to apply the extract as an economical product that can treat skin infections and there are several compounds that dominate SBG extract with the highest antibacterial activity, such as organosulfur compounds, amino acids, flavonoids and phenolics based on LC-MS analysis.